INTERPRETASI SISTEM PANAS BUMI SUWAWA BERDASARKAN DATA GAYA BERAT - Dian Nur Rizkiani; Rustadi Rustadi (Engineering Faculty Universitas Lampung, 2019)
The research of gravity on Suwawa Sub-District geothermal is done for the purposes to determine fault structure using Second Vertical Derivative (SVD) technique, create a 2D subsurface model and 3D tentative model using regional anomaly data, and interpreting Suwawa geothermal system. Data processing is done in the research include: drift correction, terrain correction, free air correction, complete Bouguer anomaly, spectral analysis, SVD analysis, 2D modeling and 3D inversion modeling and tentative model. The research results showed that the research area has low Bouguer anomaly with a range of 75.8 to 79.5 mGal values in the West and Southeast, while high anomaly with a range of 90.9 to 111.2 mGal values in the Northern and Southern, there is correlation of fault based on SVD analysis with geological fault that indicate the presence of Libungo hot springs, the inversion results indicate the presence of low density (ρ = 1.8 g/cc) which is an alluvial rocks and high density (ρ = 2.9 g/cc) which is Andesite Lava rocks, 3D tentative modeling indicate the presence of reservoir is at a depth of 2 km from the ground surface. Based on the model created, Cap Rock is located on Andesite Lava rocks with ρ = 2.9 g/cc at a depth of 1200 m and Heat Source located at a depth of 2000 m.